Hypanus longus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Hypanus longus (Garman, 1880). Longtail Stingray. To about 180 cm (70.1 in) DW (Weigman 2016). Bahía San Juanico, southern Baja California (Fitch 1953) to Ecuador, and probably to northern Peru (Chirichigno and Vélez 1998), and Islas Galápagos (Grove and Lavenberg 1997). Benthic; depth: shallow waters to at least 118 m (387 ft) (Amezcua Linares 1996), and probably deeper. Previously Dasyatis longa (Garman, 1880), we follow Last et al. (2016a) and place this species in the genus Hypanus. ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 28, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...